Neuroprotective effects of electroacupuncture on hypoxic-ischemic encephalopathy in newborn rats association with increased expression of mTOR (Bangladesh Journal of Pharmacology, 2016)
In this study, we observed the therapeutic effects of acupuncture and investigated the underlying molecular mechanisms by constructed a hypoxic-ischemic encephalopathy (HIE) animal model. In the electroacupuncture group, mTOR expression increased since 1d, and continued to rise till the 21st day. All of the differences were significantly (p